Practicing Public Pastoral Theologies in Contexts of Difference Finding Goodness in One Another - Son, Angella (2015)
My task is to discuss the challenges and promise of seminary/divinity school teaching in contexts of difference as a pastoral theologian practicing public theology. My pastoral public theological posture is finding goodness in one another and was prompted by the prevalent state of estrangement among people while acknowledging the gravity of estrangement between God and humanity, as well as self-estrangement. My response to this current societal malaise does not come from an expected trajectory (i.e., theology of sin), but from a different direction. Instead of examining what is wrong with us and what is causing the widespread estrangement in our society, I position my attention on the goodness in each of us that God has imputed, but has been wittingly or unwittingly neglected or ignored by us. For this discussion, I engage in three different areas of my work-scholarship, curriculum development, and pedagogy.
Keywords: curriculum development; Finding goodness in one another; Pastoral Theology; Pedagogy; Public Theology; Scholarship; Teaching in Theological Institutions